Avaliação qualitativa e quantitativa do potencial de reúso de água cinza em edifícios residenciais multifamiliares - Fiori, Simone (2005)
The fast growth of the urban population, of the industrialization and also the growing demand for water, as well as the imminent perspective of its scarcity, it is submitting to serious pressures the water resources and the capacity of environmental protection of a lot of cities, doing of the intended water reuse a current theme and of great importance. The water reuse, is not a new concept and it has been practiced in the whole world has many years. In literature, about the subject, there are examples of diverse forms of how can realize this reuse, where the quality is not the main parameter of requirement. Although Brazil possesses one of the largest water patrimonies of the Planet, the measure of reuse of the water becomes mainly necessary in the great urban centers, whose demand is repressed by the pollution. The possibility of substitution of part of the drinking water, for one of inferior quality, for ends non noble, reduces the demand in the springs of water. However, it need to institutionalize, to regulate and to promote the water reuse in the country, doing with that the practice grows in agreement with appropriate technical beginnings, as well as be economically viable. Thus, this work aims at to determine the quality parameters and amount of greywaters in multifamiliars residential buildings, through analyses in laboratories and of applied questionnaires the population, with the purpose of to subsidize the reduction of the consumption and to look for the sustainability of the drinking water for the rational and efficient use of the water. With the quantitative and qualitative results of the analyzed waters, it was observed that with an appropriate treatment, as the indicated for U.S.EPA, for exemple urban reuse, secondary treatment, filtration and disinfection, or still the indicated treatments for NBR 13.969/97, these waters can be reused for ends non drinking in any construction, generating economy of drinking water with reduction of the demand in the urban systems of reception, distribution and treatment of water